Power Sector Reform in Africa : Assessing Impact on Poor People - Eberhardt, Anton (World Bank, Washington, DC, 2014)
The goal of this study is to examine the impact of power sector reform on poor people in Africa by tracing the relationship between this process and certain key factors that directly affect the poor, such as access to electricity, the affordability of electricity services, quality, and reliability of supply, access to such social services as electrified clinics and schools, economic development, and net impacts on public finances. The study examines power sector reform in six African countries - Ghana, Mali, Namibia, South Africa, Tanzania, and Uganda - using sector-wide data. Broad trends across the case study countries suggest that the impacts of power sector reform on the poor are neither direct nor inevitable. Although the introduction of private actors may actually result in price increases and not necessarily expand access to electricity, reform also provides opportunities that would not otherwise exist to improve quality and reliability, expand networks, and re-direct public resources more transparently to the poor and rural communities.